The Role of Digital Payment, Peer-to-Peer Lending, and Digital Financial Literacy in Fostering Gen Z’s Micro Small Medium Enterprises Sustainability - Yuneline, Mirza Hedismarlina; Karina, Fanny (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2025)
Abstract. This study investigates the influence of Digital Financial Literacy (DFL), Digital Payment adoption, and Peer-to-Peer (P2P) Lending adoption on the Sustainability of Gen Z Micro, Small, and Medium Enterprises (MSMEs) in Bandung, Indonesia. This study is motivated by the paradox that while the national financial inclusion index exceeded the government target of 75 percent, whereas financial literacy lagged at 38 percent in 2019. This gap highlights a crucial constraint on the effective utilization of emerging FinTech by entrepreneurs. Utilizing a quantitative descriptive approach, data were collected through a questionnaire administered to 100 Gen Z entrepreneurs in Bandung, with analyses conducted using SEM-PLS. Results indicate that Gen Z respondents are on average well-literate in digital finance. Digital financial literacy and payment gateway adoption significantly effect MSME sustainability, whereas P2P lending adoption has no significant effect. Theses findings suggest that strengthening Gen Z’s financial skills and payment technologies is crucial for MSME sustainability, while trust and risk issues may limit P2P lending’s role. We recommend targeted financial education and supportive fintech policies to empower young entrepreneurs Keywords: Digital financial literacy, payment gateway, P2P Lending, MSMEs, Sustainability, Gen Z